DETERMINAN PEMILIHAN MATA PELAJARAN EKONOMI UNBK DI SMA NEGERI 18 KABUPATEN TANGERANG - Roby Zulkarnaen Alawi (Journal of Business Education and Social, 2020)
The aim of this study was to determine whether there was any influence of gender, learning achievement, teacher characteristics, family characteristics and school characteristics on the interest in selecting economic subjects at UNBK. The study decided to conduct a descriptive research design using logistic regression analysis techniques. The sample in this study was 129 students and data collection techniques used questionnaires and documentation. The result of this study was to determine whether there was any influence of gender, learning achievement, teacher characteristics, family characteristics and school characteristics on the interest in selecting economic subjects at UNBK. The study decided to design The results of this study indicate that gender, learning achievement, teacher characteristics, family characteristics and school characteristics. From the six variables at least continuing to college, family characteristics and school characteristics have a significant effect, meaning that the probability of choosing economic subjects in twelfth grade students of Social Sciences at SMAN 18 Kabupaten Tangerang is significantly influenced by these three variables.Keywords: Family Characteristics, Gender, Learning Achievement, School Characteristics, Teacher Characteristics